Dextrin nanoparticles: studies on the interaction with murine macrophages and blood clearance - Gonçalves, Catarina (2010)
The uptake of nanoparticles by cells of the mononuclear phagocytic system limits its use as colloidal drug carriers, reducing the blood circulation time and the ability to reach biological targets. In this work, the interaction between dextrin nanoparticles – recently developed in our laboratory – and murine bone marrow-derived macrophages was evaluated. Cytotoxicity and nitric oxide production were studied, using the MTT assay and the Griess method, respectively. FITC labelled nanoparticles were used to assess the phagocytic uptake and blood clearance after intravenous injection. The phagocytic uptake was analysed in vitro by confocal laser scanning microscopy and fluorescence activated cell sorting. The results show that the nanoparticles are not cytotoxic and do not stimulate the production of nitric oxide by macrophages, in the range of concentrations studied. Nanoparticles are phagocytosed by macrophages and are detected inside the cells, concentrated in cellular organelles. The blood clearance study showed that the blood removal of the nanoparticles occurs with a more pronounced rate in the first 3 h after intravenous administration, with about 30% of the material remaining in systemic circulation at this stage. Given the fairly high blood circulation time and biocompatibility, the dextrin nanoparticles are promising carriers for biomedical applications. Both applications targeting phagocytic, antigen-presenting cells (for vaccination purposes) and different tissues (as drug carriers) may be envisaged, by modulation of the surface properties.